Thermal tolerance, development, and physiological impacts of climate warming on zoea larvae of brachyuran crabs - Marochi, Murilo Zanetti [UNESP]; Duarte, Rafael Mendonça [UNESP]; Costa, Tânia Marcia [UNESP] (Elsevier, 2024)
Predicted effects of increasing ocean temperatures, due anthropogenic climate change, might be more challenging for early life history stages owing to reduced thermal tolerance. Thus, determining species responses to the projected climate warming conditions on marine ecosystems is essential to access their vulnerability. Here, we experimentally evaluated the effect of increased temperature on larval survival, development time and metabolic responses of two intertidal crab species (Menippe nodifrons and Ucides cordatus). The metabolic rate (measured as oxygen consumption), ammonia excretion and heartbeat rates were measured in standard fashion way, while the coefficient of temperature was obtained as a measure of organism's sensitivity to temperature increase. Critical thermal maximum and minimum, and thermal safety margins were also obtained. The results indicate a decrease in survival probability and development time for both species, from zoea I to zoea III stage, which was seen in higher extent to larvae of M. nodifrons. There is no significant effect of temperature increase on heartbeats and ammonia excretion rates to both species; however, increases in temperature had a differential effect on metabolic responses of two species. In addition, the critical thermal limits for the larval phase were described for the first time, suggesting that larvae of M. nodifrons are more vulnerable and have lower acclimation capacity to warming waters. Although a high sensitivity in metabolism was seen in U. cordatus, this species demonstrates higher thermal tolerance accompanied by a greater physiological plasticity. Our data emphasize that warming of coastal waters may reduce the larval survival and development time of both species, which can potentially impact its distribution and population size.
Keywords: Climate change; Larval development; Larval survival; Organism's response; Thermal stress